Cytotoxic Effect on Human Myeloma Cells and Leukemic Cells by the Agaricus blazei Murill Based Mushroom Extract, Andosan™. (7th November 2017) - Tangen, Jon-Magnus; Holien, Toril; Mirlashari, Mohammad Reza; Misund, Kristine; Hetland, Geir
Abstract : Agaricus blazei Murill is an edible mushroom of the Basidiomycetes family, which has been found to contain a number of compounds with antitumor properties, such as proteoglycans and ergosterol. In the present investigation, we show that the commercial mushroom product Andosan, which contains 82.4% Agaricus blazei Murill, together with medicinal mushrooms Hericium erinaceus (14.7%) and Grifola frondosa (2.9%), has a cytotoxic effect on primary myeloma cells, other myeloma cell lines, and leukemia cell lines in vitro. Although the exact content and hence the mechanisms of action of the Andosan extract are unknown, we have found in this investigation indications of cell cycle arrest when myeloma cell lines are cultivated with Andosan. This may be one of the possible explanations for the cytotoxic effects of Andosan.